2017
DOI: 10.1002/dev.21596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mother's voice on neonatal respiratory activity and EEG delta amplitude

Abstract: While the influence of the mother's voice on neonatal heart‐rate response and its relevant activity on cerebral cortex and the autonomic nervous system (ANS) are well known, few studies have assessed its influence on respiratory activity. We investigated the relationship among the respiration rate, the delta wave amplitudes through electroencephalography, and the basal state of ANS through the respiratory variability index while 22 full‐term neonates hear their mother's voice and an unknown voice. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…13,45 For full-term neonates, maternal voice also had beneficial effects on physiologic response. 46 These findings are consistent with our study results. To sum up, maternal voice may be an effective strategy for pain relief and physiologic stability in infants when performing painful procedures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…13,45 For full-term neonates, maternal voice also had beneficial effects on physiologic response. 46 These findings are consistent with our study results. To sum up, maternal voice may be an effective strategy for pain relief and physiologic stability in infants when performing painful procedures.…”
Section: Discussionsupporting
confidence: 94%
“…Previous study reported that maternal voice could increase the physiologic, emotional and behavioural stability of preterm infants 13,45 . For full‐term neonates, maternal voice also had beneficial effects on physiologic response 46 . These findings are consistent with our study results.…”
Section: Discussionsupporting
confidence: 93%
“…From the intrauterine environment onward, infants are exposed to human voices, particularly that of the mother, as sounds and vibrations are transmitted to the developing auditory mechanisms of the fetus [11]. The distinct impact of maternal vs. unknown adults' voices on infants' attention has been largely evidenced from the early weeks of life, affecting sucking behaviors [12], as well as the growth and functioning of the cerebral cortex and the autonomic nervous system [11,13] and eliciting sensible heart-rate responses [14]. Also, the types of parental verbalizations may play a specific role, for example, Ferrari et al [15] showed that fetuses at 25 weeks of gestation were selectively responsive to specific maternal vocalizations, exhibiting a congruent change in their mouth motor behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In 1986, DE Rumelhart and GEHinton et al proposed a neural network error backpropagation (EBP) [ 15 ] training algorithm, which solved the “exclusive OR” problem of the “perceptron” and reduced the neural network. After the 1990s, neural network methods have gradually been applied to the automatic classification and recognition of biological signals [ 16 ], and certain results have been achieved.…”
Section: Introductionmentioning
confidence: 99%